An oligomer complementary to c-myb-encoded mRNA inhibits proliferation of human myeloid leukemia cell lines. - Anfossi, G (1989)
To study the role of the protooncogene c-myb in regulating myeloid leukemia cell proliferation and differentiation, we exposed cells of the human leukemia lines HL-60, ML-3, KG-1, and KG-1a to an oligodeoxynucleotide complementary to an 18-base-pair (bp) sequence of c-myb-encoded mRNA. This treatment resulted in a significant decrease in cell proliferation in all of the lines, which was most marked in HL-60 cells. After 5 days in culture, in several separate experiments with different oligomer preparations, 75% growth inhibition was observed in c-myb antisense treated cells in comparison to untreated HL-60 cells. Two c-myb antisense oligomers of identical length with either 2- or 4-bp mismatches had no effect on cell growth nor did an 18-bp c-myb sense or myeloperoxidase antisense oligomer. The effect of a c-myc antisense oligomer (18 bp) on the growth of HL-60, KG-1, and KG-1a cells was also studied. This oligomer had much less inhibitory effect on cell proliferation than did the c-myb antisense sequence. Interestingly, although c-myc antisense treatment induced maturation of HL-60 cells while it inhibited cell proliferation, such an effect was not noted in c-myb antisense treated cells. These studies indicate that the nuclear protein encoded by the c-myb protooncogene is required for maintenance of proliferation in certain leukemia cell lines. In compared to c-myc protein suggest that, at least in HL-60 cells, c-myc amplification or N-ras activation may not be sufficient to maintain the leukemic growth in the absence of c-myb protein. These findings support the hypothesis that development and maintenance of a malignant phenotype requires a multiplicity of interrelated genetic events.